2017
DOI: 10.1007/s10661-017-6068-2
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of arsenic from water with citric acid cross-linked water hyacinth (E. crassipes) root powder

Abstract: A green and novel approach was demonstrated for successful remediation of arsenic from contaminated water by citric acid (CA) cross-linked water hyacinth root powder (RP). Different analytical techniques were used to investigate the binding and structural properties of prepared materials. Titanium dioxide played a significant role in the cross-linking process. Incorporation of CA into RP enhanced its integrity, and thus removal efficiency remained unaffected after several cyclic runs. Also the turbidity which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Another unique aspect of the pomace extract used in this study was the addition of citric acid to the water for the extraction of polyphenols from pomace. Research has shown that citric acid can be a useful complexing agent (with Fe (II) present) in the removal of arsenic from water [38,39]; however, further testing is warranted to examine the ability of citric acid to aid in the removal of arsenic from rice bran (with and without added pomace polyphenols). Additionally, both the i-As content of rice bran after the addition of blueberry pomace extract (0.295 ppm) and the total As content (0.445 ppm) were still above the 0.200 ppm maximum level in polished rice recommended in 2014 by the Codex Alimentarious Commision’s Committee on Contaminants in Foods [40].…”
Section: Resultsmentioning
confidence: 99%
“…Another unique aspect of the pomace extract used in this study was the addition of citric acid to the water for the extraction of polyphenols from pomace. Research has shown that citric acid can be a useful complexing agent (with Fe (II) present) in the removal of arsenic from water [38,39]; however, further testing is warranted to examine the ability of citric acid to aid in the removal of arsenic from rice bran (with and without added pomace polyphenols). Additionally, both the i-As content of rice bran after the addition of blueberry pomace extract (0.295 ppm) and the total As content (0.445 ppm) were still above the 0.200 ppm maximum level in polished rice recommended in 2014 by the Codex Alimentarious Commision’s Committee on Contaminants in Foods [40].…”
Section: Resultsmentioning
confidence: 99%
“…To remove arsenic from pumped groundwater, the ATUs follow chemical principles of ion exchange and membrane‐based processes (Dominguez‐Ramos et al., 2014; USEPA, 2003), oxidation (Bajpai & Chaudhuri, 1999; Katsoyiannis et al., 2008), coagulation (Jekel & Seith, 2000; Kobya et al., 2020; Kumar et al., 2004; Pokhrel et al., 2005), adsorption (Kango & Kumar, 2016; Lunge et al., 2014; Nikolaidis et al., 2003; Uddin & Jeong, 2020), etc., followed by filtration. Few advanced methods consist of phytoremediation (Kubiak et al., 2012) and bioremediation (Dadwal & Mishra, 2017; Gogoi et al., 2017; Katsoyiannis & Zouboulis, 2004; Kumari et al., 2019; Maity et al., 2021; Rahman et al., 2014; Tsai et al., 2009) of the arsenic‐contaminated water. The water treatment media in these units comprise minerals of iron and aluminum for their high sorption and co‐precipitation affinity towards arsenic (Abass et al., 2016; Bora et al., 2016; Guzmán et al., 2016; Habuda‐Stanić & Nujić, 2015; Kobya et al., 2020; Ordonez et al., 2020).…”
Section: Groundwater Treatment and Wastewater Managementmentioning
confidence: 99%
“…It has been shown, for example, that water hyacinth is a good biosorbent for heavy metals contamination and it can improve the quality of water around the plant cover (Wang et al 2012;Moyo et al 2013;Ammar et al 2014;Wanyonyi et al 2014;Matindi et al2014;Pusphe et al 2016;Feng et al 2017;Arenas et al 2018;Ting et al 2018;Sayago 2019). The remediated water that is not polluted by heavy metals can be used for various uses, for example for agricultural irrigation, so that in can increase economic income (Akinwade et al 2013;Matindi et al 2014;Canazart et al 2017;Gogoi et al 2017;Priya et al 2018;Nash et al 2019).…”
Section: Positive Economic Impacts Of Water Hyacinth In Rawapening Lake Bioremediationmentioning
confidence: 99%